2018
DOI: 10.19087/jveteriner.2017.18.4.510
|View full text |Cite
|
Sign up to set email alerts
|

Studi Histopatologi Limpa dan Bursa Fabricious Ayam Berpenyakit Tetelo (Newcastle Disease) pada Kasus Lapang (HISTOPATHOLOGY STUDIES ON SPLEEN AND BURSA OF FABRICIUS OF NEWCASTLE DISEASE CHICKHENS FROM FIELD CASE)

Abstract: Newcastle Disease is a highly contagious and very virulent avian disease in all of poultry. The aims of this study were to determine the lesions and distribution of Newcastle disease virus on spleen and bursa of Fabricous of Newcastle disease chickhens from field cases. The sample used in this study were the spleen and bursa Fabricious organ of ten cases of suspect Newcastle disease. Haematoxylin and eosin staining examination was performed determine of cell morphology and distribution of the virus by immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Replikasi strain virus ND virulen pada organ visceral akan menyebabkan kerusakan jaringan, perdarahan dan nekrosis pada saluran usus, respiratori dan caeca tonsil (Naprila & Prasetyo, 2022). Limpa yang dimiliki oleh ayam kasus mengalami pembengkakan (splenomegali) yang dipengaruhi oleh fungsi limpa bertambah di mana disebabkan oleh respon terhadap NDV yang merangsang sel-sel limfosit dalam organ limfoid untuk membentuk antibodi dalam melawan infeksi NDV (Etriwati et al, 2018).…”
Section: Analisis Dataunclassified
“…Replikasi strain virus ND virulen pada organ visceral akan menyebabkan kerusakan jaringan, perdarahan dan nekrosis pada saluran usus, respiratori dan caeca tonsil (Naprila & Prasetyo, 2022). Limpa yang dimiliki oleh ayam kasus mengalami pembengkakan (splenomegali) yang dipengaruhi oleh fungsi limpa bertambah di mana disebabkan oleh respon terhadap NDV yang merangsang sel-sel limfosit dalam organ limfoid untuk membentuk antibodi dalam melawan infeksi NDV (Etriwati et al, 2018).…”
Section: Analisis Dataunclassified
“…ND can cause damage to lymphoid tissue and macrophages. Previous studies reported that histopathologically ND causes lymphoid follicular depletion, necrosis, and apoptosis in the caecal tonsil, thymus, and bursa of Fabricius and spleen chicken ( Nakamura et al , 2008 ; Anis et al , 2013 ; Etriwati et al , 2017a ). Skeletal muscle congestion, mild intestinal erosion, and mild hemorrhagic cecal tonsils in ducks ( Eze et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%